1997
DOI: 10.1006/viro.1997.8550
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Two Subgenomic RNA Promoters for Turnip Crinkle Virusin Vivoandin Vitro

Abstract: Infection of plants or protoplasts with turnip crinkle virus (TCV), a monopartite RNA virus, results in the synthesis of the genomic RNA and two subgenomic (sg) RNAs. The transcription start site for the 1.45-kb sgRNA was previously mapped to position 2606 (J. C. Carrington, T. J. Morris, P. G. Stockley, and S. C. Harrison, (1987). J. Mol. Biol. 194, 265-276) corresponding to position 2607 in the TCVms isolate and the start site for the 1.7-kb sgRNA has now been mapped to position 2333 in TCVms. A 96-base sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
89
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 45 publications
9
89
0
2
Order By: Relevance
“…We believe that the specificity mechanism we have described may be used rather commonly in the replication of positive strand RNA viruses+ It fits observations made in mapping the genomic promoters recognized by turnip crinkle virus (TCV) RdRp in both the positive and negative sense strands of TCVassociated satellite RNA C (Song & Simon, 1995;Guan et al+, 1997), and may also apply to subgenomic RNA synthesis from this satellite RNA (Wang & Simon, 1997)+ It may apply to the RNAs replicated by Qb replicase: the well-known requirement for secondary structure might not only be in order to ensure product release from the template strands (Arora et al+, 1996), but perhaps also an expression of the specificity mechanism we have described+ Interestingly, although potential promoter elements have been described on Qb RNA, Barrera et al+ (1993) have suggested that "template selectivity may be provided by the tertiary structure and topology of the RNA, and in addition by the C-rich 39-terminal sequence+" Further, the observation that poliovirus and human rhinovirus genomes entirely lacking the 39-noncoding region upstream of the poly(A) tail (deletions of 68 and 44 nt, respectively) were capable of replication (albeit debilitated) led to the conclusion that the basic mechanism of picornavirus replication initiation may not be strictly template specific (Todd et al+, 1997)+ The observed replication of the truncated genomes might alternatively be explained in terms of a specificity mechanism like that used by TYMV RdRp+ Finally, the template preferences we have observed for TYMV RdRp are remarkably similar to the template requirements of the Mauriceville retroplasmid reverse transcriptase (Chen & Lambowitz, 1997), an enzyme that has been considered to be evolutionarily intermediate between TYMV-like RdRp's and retroviral-like reverse transcriptases (Maizels & Weiner, 1994)+ These observations suggest that it will be useful to consider the specificity principle we have described here in future searches for cis-active elements controlling RNA transcription in positive strand viruses+ We believe that this mechanism may also be found to operate in other RNA-protein interactions, such as transcript binding by the bacterial rho termination protein, for which RNA recognition criteria have proven elusive (Platt, 1994), or in the selection of splice sites in precursor mRNAs (Goguel & Rosbash, 1993;Black, 1995)+…”
Section: Applicability Of This Specificity Mechanism To Other Proteinsupporting
confidence: 68%
“…We believe that the specificity mechanism we have described may be used rather commonly in the replication of positive strand RNA viruses+ It fits observations made in mapping the genomic promoters recognized by turnip crinkle virus (TCV) RdRp in both the positive and negative sense strands of TCVassociated satellite RNA C (Song & Simon, 1995;Guan et al+, 1997), and may also apply to subgenomic RNA synthesis from this satellite RNA (Wang & Simon, 1997)+ It may apply to the RNAs replicated by Qb replicase: the well-known requirement for secondary structure might not only be in order to ensure product release from the template strands (Arora et al+, 1996), but perhaps also an expression of the specificity mechanism we have described+ Interestingly, although potential promoter elements have been described on Qb RNA, Barrera et al+ (1993) have suggested that "template selectivity may be provided by the tertiary structure and topology of the RNA, and in addition by the C-rich 39-terminal sequence+" Further, the observation that poliovirus and human rhinovirus genomes entirely lacking the 39-noncoding region upstream of the poly(A) tail (deletions of 68 and 44 nt, respectively) were capable of replication (albeit debilitated) led to the conclusion that the basic mechanism of picornavirus replication initiation may not be strictly template specific (Todd et al+, 1997)+ The observed replication of the truncated genomes might alternatively be explained in terms of a specificity mechanism like that used by TYMV RdRp+ Finally, the template preferences we have observed for TYMV RdRp are remarkably similar to the template requirements of the Mauriceville retroplasmid reverse transcriptase (Chen & Lambowitz, 1997), an enzyme that has been considered to be evolutionarily intermediate between TYMV-like RdRp's and retroviral-like reverse transcriptases (Maizels & Weiner, 1994)+ These observations suggest that it will be useful to consider the specificity principle we have described here in future searches for cis-active elements controlling RNA transcription in positive strand viruses+ We believe that this mechanism may also be found to operate in other RNA-protein interactions, such as transcript binding by the bacterial rho termination protein, for which RNA recognition criteria have proven elusive (Platt, 1994), or in the selection of splice sites in precursor mRNAs (Goguel & Rosbash, 1993;Black, 1995)+…”
Section: Applicability Of This Specificity Mechanism To Other Proteinsupporting
confidence: 68%
“…Replicases can accurately identify the correct start site for transcription of the genomic RNA, even when the site is artificially placed distal to the 3Ј end of the template (24,40,43). In addition, many viral RdRps synthesize 3Ј-coterminal subgenomic RNAs by using internal promoters located on minusstrand replication intermediates (18,25,48) that do not necessarily contain sequence or structural similarity to promoters that mediate full-length complementary-strand synthesis. Some plant viruses also provide the replication machinery for associated satellite RNAs (satRNAs), most of which share little sequence similarity with the viral genomic RNA (38).…”
mentioning
confidence: 99%
“…Deletion mapping was performed for the tombusvirus Cucumber necrosis virus (CuNV), 21 and the carmovirus Turnip crinkle virus (TCV), 15,22 and the results indicated that sequences both upstream and downstream of the initiation sites were involved in sg mRNA transcription. The working hypothesis in these studies and similar later studies 23 was that the complement of these mapped sequences acted as promoters within the full-length antigenomes, to which the viral RdRps would bind internally and initiate transcription.…”
Section: Rna Elements Involved In Sg Mrna Transcriptionmentioning
confidence: 99%
“…14 For carmoviruses, the smaller sg mRNA2 is expressed at higher levels than sg mRNA1. 15,16 These different levels and timings of sg mRNA production are likely due to "tuning" of sg mRNA synthesis in response to distinct selection pressures for their encoded proteins during viral infections.…”
Section: Rna Elements Involved In Sg Mrna Transcriptionmentioning
confidence: 99%